Frequency and causes of medication errors of nurses in - Yousefi, mahboubeh sadat; Abed Saeedi, zhila; Maleki, marzieh; Sarbakhsh, parvin (Advances in Nursing & Midwifery, 2015)
Background: Medication orders are an important part of the healing and patient care process. Considering the increasing statistics of medication errors, a study was conducted to study the frequency, type, and causes of medication errors of nurses in medical and surgical wards in different shifts of educational hospitals affiliated with ShahidBeheshti University of Medical Science in 2012. Materials and Methods:This is a descriptive study conducted on 218 nurses working at medical and surgical wards of educational hospitals affiliated with ShahidBeheshti University of Medical Science in 2012. The sampling method was stratified. Data collection tools were questionnaires. The data was analyzed by SPSS 18th version using descriptive statistics, two-sample tests, analysis of variance, and Pearson correlation coefficient. Results: The average medication errors in one monthwas 31/6 casesper nurse. Gender and shiftwork were significantly related to medication errors so that the average medication errors more in men than in women. Furthermore Statistical significant difference was observed in the number of medication errors in different shiftwork indicating that the average medication errors were the highest in the afternoon and night shifts. The average of medication errors in night shift were more than morning shift while there was no difference between the morning shift and the rotation one. Wrong time error was the most frequent one in the study. According to nurses the most important factors in medication errors are high workload, lack of nurses per patients in each ward, and fatigue. Conclusion:Based on the results of the study, it's necessary for nursing managers to pay more attention to logical proportion of patient/staff at different wards, reduction of workload and reduction of nurses" work hours because these factors can lead to their fatigue and a fall in their concentration. Keywords: medication errors, nurses, and factors